2017
DOI: 10.4314/jfas.v9i3.23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic extracts of <i>Bunium incrassatum</i> on the hematological, ovarian and uterine parameters of mature female rabbit

Abstract: This work aims to evaluate the effect of the organic extracts of Bunium incrassatum roots on some hematological parameters and histological changes of the genital tract. The study was achieved on mature rabbits of the local breed for 15 days. The animals were divided into five groups, which have daily administered 0, 25, 50, 100 and 200 mg/kg/day doses, respectively.The group with dose 0 was taken as a control. After treatment, the rabbits were sacrificed. The rabbit blood was collected in heparin tubes and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Discussion: This work's objective was to investigate the effects of a diet rich in Bunium incrassatum roots powder (15%) on mature female rats during 15 days of experimentation. Our results revealed that the increase in the final body weight of rats over their initial weight (13.8% at the end of experimentation) was not statistically significant compared to controls, as confirmed by Chentouh et al, (2017) where mature female rabbits received different doses of organic extract of B. incrassatum roots by oral gavage (25, 50, 100 and 200 mg/kg/day)during 15 days. The increase in the final body weight of mature rabbits compared to their initial weight was not statistically significant, between 12.33 and 18.47% (Chentouh et al, 2017).…”
Section: Histological Changessupporting
confidence: 52%
See 1 more Smart Citation
“…Discussion: This work's objective was to investigate the effects of a diet rich in Bunium incrassatum roots powder (15%) on mature female rats during 15 days of experimentation. Our results revealed that the increase in the final body weight of rats over their initial weight (13.8% at the end of experimentation) was not statistically significant compared to controls, as confirmed by Chentouh et al, (2017) where mature female rabbits received different doses of organic extract of B. incrassatum roots by oral gavage (25, 50, 100 and 200 mg/kg/day)during 15 days. The increase in the final body weight of mature rabbits compared to their initial weight was not statistically significant, between 12.33 and 18.47% (Chentouh et al, 2017).…”
Section: Histological Changessupporting
confidence: 52%
“…Our results revealed that the increase in the final body weight of rats over their initial weight (13.8% at the end of experimentation) was not statistically significant compared to controls, as confirmed by Chentouh et al, (2017) where mature female rabbits received different doses of organic extract of B. incrassatum roots by oral gavage (25, 50, 100 and 200 mg/kg/day)during 15 days. The increase in the final body weight of mature rabbits compared to their initial weight was not statistically significant, between 12.33 and 18.47% (Chentouh et al, 2017). A similar result was reported by Salisu et al, (2012), where the inclusion of 0, 15, 30, 45, and 60% of Daucus carota (Apiaceae) leaves' flour in the diet of five groups of rabbits for 8 weeks demonstrated that rabbits with the highest weight and the gain ratio (p>0.05) was not significantly different from control rabbits.…”
Section: Histological Changessupporting
confidence: 52%
“…However. the phytochemical analysis of roots of the plant revealed thepresence of some bioactive compounds (sucrose, oleic acid, scopoletin, scoparone and βsitosterol) Chentouh et al (2017). Studies have shown that replacing part of wheat flour with root flour like sweet potato improves the properties of the the flour and dough and the texture and sensory quality of the beard (Meng et al (2020).…”
Section: Introductionmentioning
confidence: 99%